Efektivitas Implementasi Gedsi dalam Pendidikan dan Korelasi Terhadap Kesejahteraan Pendidik - Abdurrohman, Usamah; Afifah, Mauhibah Hafizhatul; Azizah, Silvi Imro’atul; Qomarudin, Ahmad (Journal Of Gender, Child And Humanity Studies, 2023)
The GEDSI program is a development program implemented in education. This program has a primary focus on improving the quality of education in Indonesia and opening up learning opportunities for all regardless of gender or disability. This study was conducted to determine the effectiveness of the implementation of the GEDSI program on its correlation with the welfare of educators. The method used in this study is based on literature analysis and data collection through interviews and document analysis to produce a new theory called the Grounded Theory method.